Rapid rise in the incidence and clinical characteristics of pediatric inflammatory bowel disease in a South–East Asian cohort in Singapore, 1994–2015. Issue 7 (23rd July 2018) - Ong, Christina; Aw, Marion M; Liwanag, Maria J; Quak, Seng H; Phua, Kong B
Abstract : OBJECTIVES: Epidemiological studies on pediatric‐onset inflammatory bowel disease (PIBD) are scarce in South–East Asia (SEA). This study aimed to evaluate the incidence trend and clinical characteristics of PIBD in a SEA cohort in Singapore over 22 years (1994–2015). METHODS: Case records of PIBD ≤18 years from the only two tertiary pediatric hospitals in Singapore were reviewed. The mean annual incidence (MAI) of PIBD was calculated based on Singapore's age‐specific population data. RESULTS: Overall MAI of PIBD was 1.26 per 100 000 (95% confidence interval [CI] 0.56–1.96). During the first decade (1994‐2004) MAI was 0.23 per 100 000 (95% CI 0.08–0.39); this rose almost 10‐fold to 2.28 per 100 000 (95% CI 1.15–3.41) during the second decade (2005–2015). Linear regression analysis showed significant increase in MAI over the 22‐year period ( r = 0.826, P < 0001). Of the 228 patients, 61.0% had Crohn's disease (CD), 30.3% ulcerative colitis and 8.7% IBD‐unclassified, with a mdian age at diagnosis of 10.47 years and a male predominance (58.3%); 37.7% of them aged <10 years at diagnosis and 17.5% were very early‐onset IBD. In CD, 27.3% had stricturing and/or penetrating disease and 21.6% were with perianal disease. Indians had a disproportionately high representation while positive family history was rare (1.3%). CONCLUSIONS: Although PIBD is uncommon in Singapore, its incidence has risen dramatically over recent decades. A younger age of disease onset and higher proportions of perianal and stricturing/penetrating diseases suggest more aggressive disease than in Western data.